Effect of the BASNEF Model on Maternal-Fetal Attachment in the Pregnant Women Referring to the Prenatal Clinics Affiliated to Shiraz University of Medical Sciences - Marzieh Akbarzadeh; Marzieh Moattari; Maliheh Abootalebi (Mashhad University of Medical Sciences, 2017)
Background: Prenatal attachment and positive adaptation with the concept of motherhood play a pivotal role in maternal and fetal health. The present study aimed to evaluate the effect of the beliefs, attitudes, subjective norms, and enabling factors (BASNEF) model on maternal fetal attachment in the pregnant women referring to prenatal clinics. Methods: This quasi-experimental study was conducted on 100 nulliparous women in their third pregnancy trimester (36-41 weeks), who referred to the selected prenatal clinics in Shiraz, Iran during 2011-2012. Intervention was performed based on the BASNEF model in six training sessions for 90 minutes. Data collection tools were the Cranley's maternal-fetal attachment scale and BASNEF model. Data analysis was performed in SPSS version 18 using Pearson's correlation-coefficient, independent t-test, and Chi-square at the significance level of 0.05.Results: After the intervention, a significant difference was observed in the mean score of maternal-fetal attachment in the intervention group compared to the control group (P